PEMAHAMAN HUKUM EKONOMI DALAM PENERAPAN KERJASAMA KEUANGAN DALAM PERTANIAN (TINJAUAN FIQH MUAMALAH) - Kumardani Muhammad Kasim (Sekolah Tinggi Ilmu Syariah (STIS) Al-Aziziyah Sabang, 2023)
This article aims to analyze the understanding of economic law in the application of financial cooperation in the agricultural sector from the perspective of fiqh muamalah. Financial cooperation in agriculture plays a crucial role in strengthening the sustainability and development of agricultural enterprises, as well as improving the welfare of farmers. This study employs a descriptive analysis method by combining literature review and Islamic legal review approaches. Data were obtained through literature search and documents related to the understanding of economic law, financial cooperation, and agriculture in the context of fiqh muamalah. The analysis was conducted by examining the relevant principles of economic law regarding financial cooperation in agriculture and the views of fiqh muamalah scholars. The results of the analysis demonstrate that a sound understanding of economic law in the application of financial cooperation in agriculture is highly important. This includes understanding the principles of contracts, financing, profit sharing, risks, and the legal framework governing the relationship between capital owners and farmers. The fiqh muamalah perspective provides guidance on the compatibility of financial cooperation with Sharia principles and Islamic ethics in the agricultural context. In this context, this article contributes to enriching the understanding of the implementation of financial cooperation in agriculture by considering the aspects of economic law and the perspective of fiqh muamalah. This research has the potential to provide a strong foundation for the development of a financial cooperation framework that aligns with Islamic principles in agriculture, ultimately enhancing the efficiency and sustainability of the agricultural sector.Keywords:. Economic Law, Financial Cooperation, Agriculture, Review of Fiqh Muamalah